Animasi Tata Cara Penyelamatan Bencana Gempa Bumi Untuk Anak - Anak - Gita sispratiwi Faja; Nyoman Miyarta Yasa (Universitas Bumigora, 2020)
The National Agency for the Control of Britain (BNPB) noted that 515 people died from the earthquake in Lombok, West Nusa Tenggara (NTB). Seeing this problem, the author wants to make an animation of earthquake disaster relief procedures that will be used by the BPBD as an additional medium for socializing and delivering information to increase public knowledge about procedures for saving earthquake disasters, especially children. In the process of making this animation using the pipeline method which includes three stages, namely the first stage of pre-production, the second stage of production The third stage of post-production. After doing all the stages are expected to be able to produce animation procedures for earthquake disaster rescue for children. So that this animated video can be used as a media for information dissemination or information delivery by the West Nusa Tenggara Province BPBD office which is more effective for introducing elementary school students. To determine the feasibility of the animation that was made, a beta test was conducted by submitting questionnaires to 30 respondents. The results obtained are animated procedures for rescuing earthquake disasters for children to be used as media for information dissemination or delivery of information by the West Nusa Tenggara Province BPBD office.